ION MICROPROBE STUDIES OF REACTIONS IN SQUEEZE-CAST ALUMINUM-ALLOY MATRIX COMPOSITES - Soni, K; Kang, H; Grant, P; Cantor, B; Adriaens, A; Gavrilov, K; Mogilevsky, R; Levisetti, R; Tseng, M; Williams, D (1995)
An ion microprobe with high lateral resolution has been used to study the chemical reactions at the fibre/matrix interface of metal-matrix composites. During the squeeze-casting process, the Al-Si-Mg matrix reacts with the preform made of Saffil fibres (96% Al2O3, 4% SiO2). The reaction occurs mainly between the silica binder and Mg from the matrix according to SiO2 + 2Mg = 2MgO + Si. A continuous layer of MgO was formed around the fibres, even on surfaces that were not covered by the silica binder. Possible reasons are discussed for the formation of MgO in areas where binder coating was missing. In such areas, Mg reduces SiO2 that is contained in the fibre. However, the fibres (Al2O3) are not attacked by Mg. In the isolated case of fibres that were completely uncoated, no reaction products were observed at the interface. The presence of silica binder seems to be an essential requirement for this reaction to occur, When squeeze-casting is performed with sufficiently high melt temperature, Al from the matrix also reduces silica.